Competitiveness of Slovenian agro-food sector - Aleš Kuhar (Review on agriculture and rural development, 2014)
The main objective of this article is to present an overview of the Slovenian food industry economic development in the period before the Slovenian EU accession and the first five years of the EU membership. The accession to the EU was certainly the most comprehensive change of economic environment since the state gained its independence. Nevertheless, already during the pre-accession period the changes intensified restructuring processes and increased pressures to the business performance of the sector. The agro-food industrial complex, however, is among the sectors of the acceding economies for which EU enlargement traditionally brings the most radical changes. Price level and cost differences, hardly comparable production structures, but mostly disparities in types and comprehension of the economic policies required large adjustments and caused notable economic pressures. Based on a framework of economic indicators the paper tries to answer some of the most recurrent questions related to the restructuring process of Slovenian food industry in the last decade. First we present past sectoral business performance using the appropriate mezzoeconomic accountancy indicators, whereas in the central part of the paper four key restructuring determinants are analysed and commented. The determinants are formulated into the four relevant questions dealing with cost-price developments, relations in the Slovenian agro-food chain, developments of the international trade and trends in the budgetary transfers to support competitiveness. Results confirm that the economic restructuring which had been hindered in the Slovenian food industry during the last decade has been triggered radically after EU accession. This brought to the termination of favourable economic conditions in the highly protected domestic market and deteriorated radically the business performance, and only those food companies which will restructure proactively will sustain in the EU markets.